Depositional processes on oceanic island shelves – Evidence from storm‐generated Neogene deposits from the mid‐North Atlantic. Issue 7 (10th August 2013) - Meireles, Ricardo P.; Quartau, Rui; Ramalho, Ricardo S.; Rebelo, Ana C.; Madeira, José; Zanon, Vittorio; Ávila, Sérgio P.; Trofimovs, Jess
Abstract Oceanic islands – such as the Azores in the mid‐North Atlantic – are periodically exposed to large storms that often remobilize and transport marine sediments along coastlines, and into deeper environments. Such disruptive events create deposits – denominated tempestites – whose characteristics reflect the highly dynamic environment in which they were formed. Tempestites from oceanic islands, however, are seldom described in the literature and little is known about storm‐related sediment dynamics affecting oceanic island shelves. Therefore, the geological record of tempestite deposits at oceanic islands can provide invaluable information on the processes of sediment remobilization, transport and deposition taking place on insular shelves during and after major storms. In Santa Maria Island (Azores), a sequence of Neogene tempestite deposits was incorporated in the island edifice by the ongoing volcanic activity (thus preserved) and later exposed through uplift and erosion. Because it was overlain by a contemporary coastal lava delta, the water depth at the time of deposition could be inferred, constituting an excellent case‐study to gain insight on the still enigmatic processes of insular shelf deposition. Sedimentological, palaeontological, petrographic and palaeo‐water depth information allowed the reconstruction of the depositional environment of these sediments. The sequence typifies the characteristics of a tempestite (or successive tempestites) formed at ca 50 m depth, in a steep, energetic open insular shelf, and with evidence for massive sediment remobilization from the nearshore to the middle or outer shelf. The authors claim that cross‐shelf transport induced by storm events is the main process of sediment deposition acting on steep and narrow shelves subjected to high‐energetic environments, such as the insular shelves of open‐sea volcanic islands.